The students’ Perspectives towards Online Learning during the Pandemic Covid-19 among 5 top Asian Countries - Gunawan Tambunsaribu; Lisbeth Sirait (South Sulawesi Education Development (SSED), 2024)
In connection with distance learning for the past 2 years, the researcher wants to know the problems experienced by students in various countries in Asia. The reason for choosing these 5 countries as data sources is because these 5 countries are included in 5 of the top 10 countries in education in Asia. This research uses a descriptive research method. This research aims to find out the barriers encountered by students in 5 top Asian Countries during Online Learning during the Pandemic Covid-19 and to find out the same common barriers experienced by the students among the 5 top Asian countries. The data are taken from some researchers’ findings who conducted research related to the experiences of students in online learning during the pandemic Covid19 in 5 different countries in Asia namely Indonesia, Singapore, China, Japan, and India. The researcher uses line-by-line coding. The researcher uses thematic analysis. Based on the data gained from several previous researchers, the researcher found out same barriers encountered by the students in 5 Asian countries. The researcher then categorized the same barriers into four groups namely technological device barriers, learning system barriers, Internet accessibility barriers, and students’ outer and inner motivation.